Highway access and human capital investments in the rural regions of the People's Republic of China - Han Li; Guochang Zhao; Zhaoyue Teng (Asian Development Bank Institute (ADBI), 2019)
The People's Republic of China (PRC) has made massive investments since the late 1990s in highway infrastructure, connecting its rural and urban regions. In this paper, we study the impact of highway investments on the educational choices in rural PRC. Because enhanced connectivity facilitates people's move, the poor in rural regions can gain access to a larger labor market, altering the opportunity costs of educational investment. Using 2005 population census data, we find that highway access significantly reduces the enrollment rate of senior high schools in rural PRC by 9%, but it does not affect the enrollment rates of both junior high and elementary schools, whose students are typically under the age of 16. This negative effect is more significant on students in rural regions than in urban regions.
Keywords: R41; R42; I26; 330; connectivity; educational investment; enrollment rate; highway investment; transport infrastructure; People's Republic of China